Cultural Commitments and Gender Parity: Human Rights as Implicit Religion - Walters, Barbara R. (Implicit religion, 2016)
The research reported herein follows closely on the work of Wade M. Cole and American feminist scholars, such as Christine Bose, Patricia Hill Collins, and Bandana Purkayastha. The empirical analysis uses United Nations data to examine the likelihood of a nation ratifying the Convention on the Elimination of All Forms of Discrimination against Women (CEDAW) and its Optional Protocol (OP), which amplifies the enforcement provisions, based on the extent to which gender parity is embedded in the religious, cultural, economic, and political institutions of the country. Countries with high scores on indicators of gender equality and female institutional participation are more likely to ratify both the CEDAW and the OP. The data analysis produces statistically significant relationships among key indicators of gender parity within a country, its dominant religion, and the likelihood of ratification of the CEDAW and the OPCEAFDW, with higher levels of significance for the OP. The research and findings point to existential paths within, across, and extraneous to more ordinary religious, political, and economic groupings--paths that legal texts and concerted actions invest with ultimate meaning and which are thereby appropriately cast as a form of implicit religion.